Contemporary Issues in Bank Financial Management. - Simon Grima; Frank Bezzina (Contemporary Studies in Economic and Financial Analysis,, 2016)
Contemporary Issues in Financial Services special edition includes studies by the University of Malta, MSc Banking and Finance graduates and the respective lecturers, on financial services within particular countries or regions and studies of particular themes such as credit risk management, fund management and evaluation, forex hedging using derivatives and sovereign fixed income portfolios.